Challenging the Hegemony of the Grand Paradigm of Social Movement Studies: A Review of Paradigmatic Weaknesses - Joni Rusmanto; Ester Sonya Ulfarita; Muhammad Farid (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2023)
The study of social movements today is dominated by three grand paradigms (grand theory) in the 1980s, and even in Indonesia since the 70s. The three major paradigms of study are the